A terrible country a novel - Gessen, Keith 1975- (Fitzcarraldo Editions, 2018)
""A cause for celebration: big-hearted, witty, warm, compulsively readable, earnest, funny, full of that kind of joyful sadness I associate with Russia and its writers." ...George Saunders, Man Booker Prize-winning author of Lincoln in the Bardo. A literary triumph about Russia, family, love, and loyalty...the first novel in ten years from a founding editor of n+1 and author of All the Sad Young Literary Men. When Andrei Kaplan's older brother Dima insists that Andrei return to Moscow to care for their ailing grandmother, Andrei must take stock of his life in New York. His girlfriend has stopped returning his text messages. His dissertation adviser is dubious about his job prospects. It's the summer of 2008, and his bank account is running dangerously low. Perhaps a few months in Moscow are just what he needs.